Design, analysis and fabrication of portable washing and drying machine / Muhammad Zarif Abdul Aziz - Abdul Aziz, Muhammad Zarif (2022)
Washing and drying clothes are chores, yet we do not have many alternatives to do so. For a family person, using washing machine is a way to wash clothes, as it lessens the burden. Unfortunately, washing machine is not accessible to everyone and the other way to deal with dirty clothes is wash by hands. One of the affected groups are hostel students – washing machine is very limited to them. This project is here to help the less privilege ones without washing machine to be able to wash clothes in a lot easier way by using a portable washing and drying machine. This project goes through many phases and aspects to fill the customers need based on recommendation and survey from every layer of life. All the findings are then turn into ideas to finalize the design and model for this project.